2012
DOI: 10.1007/s00216-012-6255-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of 2-methylthiazolidine-4-carboxylic acid, a condensation product of cysteine and acetaldehyde, in human blood as a consequence of ethanol consumption

Abstract: Acetaldehyde is a strongly electrophilic compound that is endogenously produced as a first intermediate in oxidative ethanol metabolism. Its high reactivity towards biogenic nucleophiles has toxicity as a consequence. Acetaldehyde readily undergoes a non-enzymatic condensation reaction and consecutive ring formation with cysteine to form 2-methylthiazolidine-4-carboxylic acid (MTCA). For analytical purposes, N-acetylation of MTCA was required for stabilization and to enable its quantification by reversed-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Indeed, we detected hydroquinone in 24.1% yield after the one-pot reaction. It has been reported that the condensation of acetaldehyde with cysteine in water give 2-methylthiazolidine-4-carboxylic acid while retaining the original configuration of the cysteine stereocenter 31 , and that 2-thiazolines can be synthesized from 2-thiazolidines by Ru/PPh 3 or Ru/TMEDA-catalysed oxidation with TBHP at ambient temperature 32 . These results are consistent with the fact that the original configuration of the cysteine stereocenter was retained through the formation of thiazoline moiety in the one-pot reaction ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we detected hydroquinone in 24.1% yield after the one-pot reaction. It has been reported that the condensation of acetaldehyde with cysteine in water give 2-methylthiazolidine-4-carboxylic acid while retaining the original configuration of the cysteine stereocenter 31 , and that 2-thiazolines can be synthesized from 2-thiazolidines by Ru/PPh 3 or Ru/TMEDA-catalysed oxidation with TBHP at ambient temperature 32 . These results are consistent with the fact that the original configuration of the cysteine stereocenter was retained through the formation of thiazoline moiety in the one-pot reaction ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[33] MTCA is an endogenous product that is detected in the blood after a moderate ethanol dose (0.5 g/kg). [34] Furthermore, it has been shown that MTCA can serve as a prodrug for L-cysteine and thus protect mice against acetaminophen toxicity. [35] Under the present study conditions, sufficiently high L-cysteine levels for acetaldehyde neutralisation were achieved in the gastric juice at 10-20 min after L-cysteine (Acetium) capsule intake.…”
Section: Discussionmentioning
confidence: 99%
“…DMB was developed to improve the sensitivity of fluorescence detection, and has a structure similar to that of OPD. As shown in Figure 11, we quantified α-keto acids in chronic myeloid leukemia cells to investigate the role of BCAT1 [73]. The concentrations of six α-keto acids were between 1.55 and 316 pmol per 106 cells and LODs were within 1.3 and 5.4 nM, being three-fold higher than that of OPD.…”
Section: α-Keto Acids and Their Metabolitesmentioning
confidence: 99%
“…2-Methylthiazolidine-4-carboxylic acid (MTCA, Figure 14) is produced by the reaction of acetaldehyde and cysteine, and it is a biomarker for recent alcohol consumption. MTCA has been derivatized with acetic anhydride and then analyzed by reversed-phase LC-ESI-MS [73]. Free MTCA is unstable under physiological conditions as it is readily hydrolyzed.…”
Section: Carboxylic Acids Containing a Thiazole Ringmentioning
confidence: 99%